Leveraging Marketing Strategies For The Growth of Tlocor Marine Tourism in Sidoarjo, East Java - Zainal Abidin; Wahyu Handayani; Mentari Puspa Wardani; Karina Regita Cahyanti; Mochammad Choiri Assydiqi; Aliflamita Marstati Nur Rizky; Didik Heryono; Yona Yuliano Prestisia (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Marine tourism utilizes coastal and marine environments as primary attractions. Since the Covid-19 pandemic, Tlocor Marine Tourism in Sidoarjo Regency has experienced fluctuating, yet generally declining, visitor numbers.Purpose: The purpose of this study is to formulate effective marketing strategies that focus on digital technology utilization, enhanced promotion, destination branding, and the development of innovative, sustainable tourism products.Design/methodology/approach: A qualitative descriptive method was employed, involving four key informants from Tlocor Marine Tourism management. Data were collected through in-depth interviews and analyzed using SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix).Findings/Result: The results indicate that Tlocor Marine Tourism falls into Quadrant III of the SWOT matrix, suggesting a turnaround (WO) strategy to minimize weaknesses and leverage available opportunities. Seven alternative strategies emerged from this analysis, with QSPM identifying the recruitment of professional experts in marketing and tour guiding as the top priority.Conclusion: The study concludes that Tlocor Marine Tourism requires strategic improvements focused on professional marketing, innovation, and digital promotion. The top priority identified is recruiting qualified marketing personnel and tour guides to enhance visibility, improve visitor experience, and support sustainable growth. Originality/value (State of the art): This research presents a structured model integrating SWOT and QSPM for post-pandemic marine tourism recovery, emphasizing digital marketing, destination branding, and sustainable product innovation as key drivers for boosting competitiveness. Keywords: marine tourism, marketing strategy, SWOT, QSPM, digital marketing